Duration of Analgesia and Blood Pressure by Giving Midazolam 2 mg Compared to Fentanyl 25 mcg in Hyperbaric Bupivacaine 10 mg During Cesarean Delivery - Sitanggang, Ruli Herman; Harniati, Siti; Redjeki, Ike Sri (Perdatin Pusat, 2015)
Pain free episode after Cesarean deliveryis needed by the mother to take care the baby. Opioid is the most common adjuvant used in spinal anesthesia, but still has unpleasant side effects, while Midazolam 2 mg is known to prolong analgesia. This study was using randomized double-blind experimental design. The subject of this study is 40 pregnant women with ASA II who underwent Cesarean delivery with spinal anesthesia. Research subjects are divided into 2 groups of study. The first group was given a combination of Fentanyl 25 mcg + 0.5% Bupivacaine 10 mg (BF) while the second group was given Midazolam 2mg+0,5% Bupivacaine 10 mg (BM). The duration of analgesia in 2 groups was assessed using a numeric rating scale (NRS). Then the data were analyzed using T-test, Mann Whitney test and Chi square test. The results showed no significant difference in both groups in a decrease of systolic blood pressure (p>0.05). Duration of analgesia in Midazolam group is 217.5 (39.32) minutes longer than Fentanyl group 124.0 (10.83) minutes. The conclusion is additional Midazolam 2 mg may prolong analgesia compared with Fentanyl 25 mcg without a decrease in blood pressure in Caserean delivery.